Are the Periods of Currency Collapse an Impediment to Entrepreneurship and Entrepreneurial Haven? Evidence from Regional Comparison - Rafindadi, Abdulkadir Abdulrashid; Yusof, Zarinah (International Journal of Economics and Financial Issues, 2014)
Currency collapse, exchange rate misalignment and macroeconomic volatility, are key vices that pose a significant threat to entrepreneurial quality, prosperity and survival. Following to this, and using the philosophies and concepts of the catastrophe theory we show by means of theoretical and conceptual arguments how these factors are impeding the entrepreneurial survival prospects. From these conceptual and theoretical analyses and using a graphical representation, we predict the gaps that could be significant multiplicities of an entrepreneurial haven using the comparative evidence of three regions, namely Africa, Asia and the Middle East. The findings of the study established that the period of currency collapse has been a strong impediment to entrepreneurial activities; in addition to this, the conceptual and theoretical analysis enable us to discover that, in theory, the establishment of a common position that could be an entrepreneurial haven is almost impossible. In contrast to this theoretical finding, while using the empirical data provided by the World Bank and by means of graphical representation, we found how the African region could be a confluence of multiplicities of the entrepreneurial haven comparable with the rest of the two regions. The study concludes with the recommendation that for an entrepreneurial haven to persist across the region, the Green Entrepreneurial (GE) process should be put into practice in order to ensure a successful, efficient and effective exploitation of opportunities in the identified haven. Keywords: Currency collapse; linear and non-linear; green entreprenology. JEL Classifications: F3; F31; G32; L26; M16; M21